UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PERKALIAN MELALUI MEDIA JENDELA PAPER DAN TALINTAR SISWA KELAS IV A SDN BLOTONGAN 02 - Diyarotun Nahara; Antonius Wahyana; Boedi Ngali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education in Indonesian has become a necessity for every individual who wishes to develop and achieve their desired future. However, this goal cannot be attained if learning outcomes do not meet the required standards of mastery. Based on observations in class IV A and interviews with the classroom teacher, it was found that there were issues during the learning process that had a significant impact on students’ mastery of the material. Specifically, most students in class IV A experienced difficulties in understanding the material and solving multiplication problems. The factors contributing to this issue include the students’ confusion understanding the concept of multiplication. This research aims to improve the learning outcomes of fourth-grade students in class IV A on the topic of multiplication operations through the use of Jendela Paper and Talintar learning media at SDN Blotongan 02, Salatiga. This study employed the Collaborative Classroom Action Research method, with a research design consisting of for stages: planning, acting, observing, and reflecting. The results showed an improvement from the pre cycle, ciycle I. And cycle II, incrasing from 42% to 53%, with a final increase reaching 84%.